2006
DOI: 10.1038/sj.jid.5700429
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptide Control Mechanisms in Cutaneous Biology: Physiological and Clinical Significance

Abstract: The skin as a barrier and immune organ is exposed to omnipresent environmental challenges such as irradiation or chemical and biologic hazards. Neuropeptides released from cutaneous nerves or skin and immune cells in response to noxious stimuli are mandatory for a fine-tuned regulation of cutaneous immune responses and tissue maintenance and repair. They initialize host immune responses, but are equally important for counter regulation of proinflammatory events. Interaction of the nervous and immune systems oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
133
0
9

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 185 publications
(142 citation statements)
references
References 66 publications
(125 reference statements)
0
133
0
9
Order By: Relevance
“…While this likely is of relevance only in a small minority of AA patients, increasing insight into the importance of the brain-skin connection, e.g., in the control of cutaneous neurogenic inflammation (91)(92)(93)(94)(95)(96), encourages one to consider the potential impact of neuroendocrine factors on AA. Murine stress models demonstrate nerve growth factor (NGF)-, substance P-, and mast cell-dependent inhibitory effects of stress on hair growth (93)(94)(95)(96). In mice, stress-induced upregulation of NGF seems to stimulate substance P synthesis in dorsal root ganglia and prematurely induces catagen development (92)(93)(94)(95).…”
Section: Aa and Stress: The Neuroendocrine-immune Hypothesismentioning
confidence: 99%
“…While this likely is of relevance only in a small minority of AA patients, increasing insight into the importance of the brain-skin connection, e.g., in the control of cutaneous neurogenic inflammation (91)(92)(93)(94)(95)(96), encourages one to consider the potential impact of neuroendocrine factors on AA. Murine stress models demonstrate nerve growth factor (NGF)-, substance P-, and mast cell-dependent inhibitory effects of stress on hair growth (93)(94)(95)(96). In mice, stress-induced upregulation of NGF seems to stimulate substance P synthesis in dorsal root ganglia and prematurely induces catagen development (92)(93)(94)(95).…”
Section: Aa and Stress: The Neuroendocrine-immune Hypothesismentioning
confidence: 99%
“…Recent studies of vertebrates revealed that skin is a prominent target of neuroendocrine signals that profoundly impact skin biology, including immunity (Arck et al, 2006;Peters et al, 2006). For example, the neuroendocrine system controls the production and secretion of antimicrobials by the epidermis (Aberg et al, 2007).…”
Section: Neuroendocrine Regulation Of the Epidermal Immune Responsementioning
confidence: 99%
“…CGRP is a 37-amino acid peptide expressed by neurons and endocrine cells in different tissues [11]. Two isoforms of the CGRP peptide have been described: alpha-CGRP, which is formed by the alternative mRNA splicing of the calcitonin gene located on chromosome 11; and beta-CGRP, which is encoded by a different, but closely related gene [11][12][13][14][15][16][17]. Alpha-CGRP and beta-CGRP differ from each other by three amino acids in humans and by one amino acid in rats [13,15], and exhibit overlapping biological actions [16].…”
Section: Introductionmentioning
confidence: 99%